NATIONAL POET OF UZBEKISTAN ENAHON SIDDIKOVA THE FRIEND "SONG ABOUT MOTHER" (Archive of Conferences, 2020)
People's poet of Uzbekistan, multi-talented Enakhon Siddikova is a mature representative of modern Uzbek literature, a great artist of words. This article examines the poet's vocabulary, linguopoetic features of the epic "Song about mother".